Klasterisasi Minat Baca Mahasiswa Menggunakan Metode K-Means - Rosman, Edwar; Ikhsan, Fathurrahman Kurniawan; Pernanda, Anggri Yulio (JURTEII: Jurnal Teknologi Informasi, 2022)
What can do one of the ways to increase student interest in reading by increasing the collection of books in the Kerinci IAIN library. But so far, determining the collection of books to be added is still done manually, so it takes a long time besides that the process of adding books which refers to the statistics of borrowing the most books, makes the collection of books less diverse. For this reason, a book collection clustering method is needed using the k-Means method to obtain optimal results. Book collections are grouped into 3 clusters that are, considerations that need to be added, priorities to be added, and not need to be added can be a reference for librarians in maximizing the process of adding book collections.